Reading the game. How to measure and improve tactical skills in team sports - van Maarseveen, M. J. J. (2018)
CHAPTER 1 General introduction CHAPTER 2 Pattern recall skills of talented soccer players: two new methods applied CHAPTER 3 System for notational analysis in small-sided soccer games CHAPTER 4 Perceptual-cognitive skill and the in situ performance of soccer players CHAPTER 5 In situ examination of decision-making skills and gaze behaviour of basketball players CHAPTER 6 Self-controlled video feedback on tactical skills for soccer teams results in more active involvement of players CHAPTER 7 Epilogue